1992
DOI: 10.2176/nmc.32.942
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interferon-β, ACNU, and Radiation Therapy in Pediatric Patients with Brainstem Glioma

Abstract: Sixteen pediatric patients with brainstem glioma were treated with a combination of interferon-beta, 1-(4-amino-2-methyl-5-pyrimidinyl)-methyl-3-(2-chloroethyl)-3-nitroso ure a hydrochloride (ACNU), and radiation therapy (IAR therapy). All patients received 1-1.5 million IU/day of interferon-beta intravenously for 1 week of each 6-week cycle. In addition, ACNU (2-3 mg/kg) was given on the 2nd day of each cycle. Conventional focal irradiation (1.5-2 Gy/day for 5 days to a total dosage of 40-60 Gy) was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A more promising result was reported by Wakabayashi et al [19] in 16 pediatric patients with brain stem gliomas treated with P-interferon, ACNU and radiation therapy. Conventional radiation therapy was given to a total dose that ranged between 4,000 and 6.000 cGy.…”
Section: Restorative Immunotherapymentioning
confidence: 73%
“…A more promising result was reported by Wakabayashi et al [19] in 16 pediatric patients with brain stem gliomas treated with P-interferon, ACNU and radiation therapy. Conventional radiation therapy was given to a total dose that ranged between 4,000 and 6.000 cGy.…”
Section: Restorative Immunotherapymentioning
confidence: 73%
“…58,112,120 In 1 study, investigators explored the role of the administration of high-dose busulfan and thiotepa after conventional radiotherapy in 35 patients with diffuse pontine gliomas. 15 The median survival time was 10 months, which was no better in comparison with radiotherapy alone.…”
Section: Chemotherapy Immediately Following Radiotherapymentioning
confidence: 99%
“…One of the most popular topics in this field is the interferon, which unfortunately yielded limited and problematic results. Wakabayashi et al (50) who added interferon-α to chemotherapy and RT reported 3 complete and 9 partial responses in a cohort of 16 diffuse BSG patients, and the responders had a median survival times better than the frequently reported <10 months period. In contrast, Packer et al (51) was not able to confirm this promising outcome in a further phase I/II study in 32 BSG patients, rendering the role of immunotherapy questionable.…”
Section: Chemotherapy and Immunotherapymentioning
confidence: 92%